Ameliorative effects of vitamins C and E on tenofovir/nevirapine-induced hepatorenal oxidative stress in albino rats - Adikwu, Elias; Apiakise, Williams (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2016)
Background and Objectives: Oxidative stress has been implicated in xenobiotic-induced hepatorenal toxicity. This research was designed to investigate the effects of vitamins C and E on the baseline and tenofovir/nevirapine-induced liver and kidney levels of superoxide dismutase (SOD), glutathione (GSH), catalase (CAT) and malondialdehyde (MDA) in male albino rats. Materials and Methods: Forty five male albino rats were used for this study. The rats were divided into groups A – I of 5 rats each. Group A (placebo control) and group B (solvent control) were orally treated with water and arachis oil respectively. Groups C – F were orally treated with vitamins C, E, vitamins C and E, and tenofovir/nevirapine respectively. Groups G– I were pretreated with vitamins C, E and vitamins C and E prior to treatment with tenofovir/nevirapine respectively. Rats were sacrificed after treatment for 30 days; liver and kidneys were collected and evaluated for the above parameters. Results: Significant (p<0.05) increases in the baseline levels of liver and kidney SOD, GSH, and CAT with decreases in MDA levels were obtained in vitamins C and E treated rats when compared to control. On the contrary, treatment with tenofovir/nevirapine significantly (p<0.05) decreased liver and kidney SOD, GSH, and CAT levels with increases in MDA levels when compared to control. However, all tenofovir/nevirapine -induced alterations were abrogated in rats pretreated vitamins C and E. Abrogation was most pronounced in rats pretreated with combined doses of vitamins C and E. Conclusion: Observations in the present study could be attributed to the inhibitory effects of vitamins C and E on the oxidative activity of tenofovir/nevirapine in the liver and kidney of treated rats.